Moesin expression is correlated with its involvement in patients with Behcet’s disease - Hussain, Muhammad (Arch Med Sci, 2020)
INTRODUCTION: Behcet’s disease (BD) is a rare, chronic autoimmune disorder of unknown etiology. Although the profile of autoantibodies for this disease is not yet completely understood, because of better disease recognition, its prevalence is increasing throughout the world. Among ERM proteins (ezrin/radixin/moesin), moesin is a member of a family which is involved in autoimmune diseases. The aim of this study is to confirm whether moesin is a potential anti-endothelial cell autoantigen (AECA) in Hans Chinese BD patients. MATERIAL AND METHODS: First, a full length recombinant human moesin protein was over-expressed and purified. Second, it was identified by mass spectrometry and then purified moesin was used to perform Western blotting, immunoprecipitation and ELISA with confirmed BD patients. Finally, in vitro cytotoxicity experiments were conducted with anti-moesin antibodies by the resazurin reduction assay method. RESULTS: : Purified moesin protein was successfully expressed and then its antigenicity was confirmed by Western blotting and immunoprecipitation techniques. Anti-moesin antibodies were detected in approximately one-third (38%) of BD patients by ELISA and the reactivity of BD serum IgG antibodies against moesin was found to be significantly higher than HC (p < 0.0001). Moreover, in order to validate our results, cytotoxicity experiments also confirmed that anti-moesin antibody had a significant inhibitory effect on endothelial cell activity. CONCLUSIONS: Expression is correlated with the involvement of moesin as an autoantigen in BD pathology, which is a new finding. It might be a new candidate biomarker in the Han Chinese population.